Research Progress of AR Gene Family in Prostate Cancer Therapy - Maham Khan (Annals of Urologic Oncology)
Prostate cancer (PCa) is a malignancy originating from the epithelial cells of the prostate gland, strongly influenced by androgens, and is one of the most common cancers in men. Androgen deprivation therapy (ADT) is the primary treatment for prostate cancer. However, after prolonged ADT treatment, nearly all patients experience an increase in prostate-specific antigen (PSA) levels and tumor regrowth. The regrowth is primarily driven by the reactivation of androgen signaling pathways within the tumor cells, leading to the development of castration-resistant prostate cancer (CRPC). The overall survival for patients with CRPC is typically less than two years. The reactivation of androgen signaling after ADT is a key mechanism leading to the progression of CRPC. In particular, abnormal expression of androgen receptor (AR) family genes, particularly AKR1C3 and AR-V7, are beleived to play central roles in the emergence of CRPC. Beyond hormonal factors, various molecular mechanisms contribute to the development of castration resistance, such as genetic mutations and the role of the tumor microenvironment. Additionally, dysregulation of signaling pathways and interactions between tumor cells and the surrounding matrix furrher promote tumor survival and growth, even in the absence of androgens. Understanding these mechanisms is essential for developing more effective treatment strategies for CRPC.